Investment climate, capabilities and firm performance Evidence from the world business environment survey - Batra, Geeta (OECD Publishing, 2008)
The World Business Environment Survey (WBES) provided a unique look at the impact of the investment climate on enterprise performance, employing a standard core questionnaire to more than 10 000 firms in 80 countries between late 1998 and mid-2000. This paper examines results of a special module of the survey administered in 28 of the WBES countries that focused on issues of competition, trade and firm capabilities in terms of technology and worker education and training. It confirms that key attributes of the investment climate such as corruption, financing, tax administration, regulations and policy uncertainty all matter in explaining firm performance as measured by sales growth, employment growth and investment growth. Further, excessive labour regulation is negatively associated with both employment and investment growth. The new data on firm capabilities suggest that firm investments in technology and skills are also critically associated with firm performance. Investment in technological capacity strongly relates to sales growth, while international technological acquisition relates clearly to employment and investment growth. Training matters as well, and it is quite clear that investments in private training services are significantly associated with all dimensions of firm growth. What is equally clear is that public training bears no significant relationship with firm performance. Firms that make no investments in training appear disproportionately influenced by three types of market failure. This link has direct implications for governments as they shape technology policy and training policy